Teaching higher order thinking skills in the English first additional language learning classroom : a case of five intermediate classrooms in Mankweng Circuit - Magwele, Peter (University of Limpopo, 2019)
There is a universal consensus among educationalists and cognitive development theorists that integration of higher order thinking (HOT) in language teaching has farreaching positive implications in learners‘ future. Their extensive body of research clearly indicates the interrelationship between language and thinking. It shows that to develop well-rounded learners who can later deal capably with varying demands of the 21st century, teaching them linguistic and cognitive skills concurrently is a prerequisite. However, there is still a dearth of language teaching classroom-based data to be collected to ascertain which language pedagogic practices promote thinking or not. Hence, a qualitative exploratory case study was conducted to address this gap. The study was undertaken in five intermediate English FAL classes in Mankweng circuit. The aim was to establish whether HOT is encouraged in the intermediate English FAL classes. The study used two data analysis techniques: firstly, Tesch‘s inductive coding technique was used to analyse semi-structured interview results sourced from five English FAL teachers. They were sampled for the study to assess their conceptualisation of HOT and its application in their language classes. Contrastingly, Anderson and Krathwohl‘s (2001) framework was used to analyse one Grade 4 English workbook. To determine if its exercises‘ instructional verbs were promoting HOT or not; to check if the questions in its exercises were equally distributed over all the six levels of Bloom's revised Taxonomy of the cognitive domain; and to evaluate if there was an incremental introduction of HOTs in its exercises through the year. The results revealed the following: the five teachers could not conceptualise HOT and showed poor knowledge of how to teach it in their classes. The instructional verbs did not comprehensively encourage HOT; those which did were only pitched at the third level of thinking i.e. apply; most of the questions were in favour of low order thinking and there was little incremental introduction of the three top levels of Bloom‘s revised taxonomy in Grade 4 English FAL workbook specifically analyse, evaluate and create/design. Key words: High order thinking skills, cognitive domain, high order thinking and Bloom‘s revised taxonomy.
Thesis (M. A. (English Studies)) --University of Limpopo, 2019
Keywords: High order thinking skills; Cognitive domain; High order thinking and Bloom‘s revised taxonomy; Creative thinking; Artificial intelligence; Fluency (Language learning)